Hypoxia impedes differentiation of cranial neural crest cells into derivatives relevant for craniofacial development - Theresa Schmid; Gabriele Rodrian; Elke Bachmann; Alexander Kohler; Michael Wegner; Lina Gölz; Matthias Weider (Open Biology, 2025)
Orofacial clefts are the second-most prevalent congenital malformation. Risk factors are multifactorial and include genetic components, but also environmental factors. One environmental factor is hypoxia during pregnancy, caused for instance by tobacco smoking, medication or living at high altitudes. We here show that hypoxia has only modest effects on proliferating cranial neural crest cells (CNCC), but dramatically influences their differentiation potential. We detected massive perturbations in their differentiation to chondrocytes, osteoblasts and smooth muscle cells. The transcriptional induction of the majority of regulated genes during each of these processes was grossly impaired by hypoxic conditions, as evidenced by genome-wide transcriptomic analyses. These hypoxia-attenuated genes include several orofacial cleft risk genes. Among these, we bioinformatically identified the hedgehog co-receptor Boc and the cysteine dioxygenase Cdo1 as two central genes that display hypoxia-attenuated induction during all three differentiation pathways and that are relevant during craniofacial development. Moreover, several components of signalling pathways between undifferentiated CNCC and their derivatives, as well as components of signalling pathways from CNCC to epithelial cells, were affected by hypoxia. Our analyses reveal a drastic influence of hypoxia on the differentiation potential of CNCC as a possible cause for the occurrence of orofacial clefts.